Detection of dopamine using glassy carbon electrodes modified with AgNPs synthetized with Monteverdia ilicifolia extract - Humacayo, Francielle Schremeta; Espinoza, Joel Toribio; de Paula, Josiane de Fátima Padilha; Lopes, Luma Clarindo; Pessoa, Christiana Andrade; Magalhães, Cássia Gonçalves (Eclética Química, 2023)
This work reports a new application for a well-known medicinal plant used in Brazil. The green synthesis of silver nanoparticles (AgNPs) using the aqueous extract of Monteverdia ilicifolia (MI) leaves as stabilizing and reducing agent is described. The AgNPs-MI obtained were characterized by UV-VIS, FTIR, and Raman spectroscopies, DLS, zeta potential and FEG-SEM, which demonstrated that M. ilicifolia was effective at capping the AgNPs, yielding stable suspensions. These nanoparticles were deposited on glassy carbon electrodes, and they were efficiently applied as electrochemical sensors for the determination of dopamine (DA) using square wave voltammetry (SWV). The AgNPs-MI improved the electrochemical properties of the electrodes and enhanced their electroanalytical performance. The developed sensing device presented detection and quantification limits equal to 0.52 and 1.74 μmol L–1, respectively, towards DA determination. The proposed electrochemical sensor quantified this neurotransmitter successfully, confirming its potential as a new promising analytical detection tool for DA quality control.